Analisa Hubungan Faktor Personal dan Manajemen K3 Terhadap Tindakan Tidak Aman dan Kecelakaan Kerja pada Proyek Konstruksi Indonesia Satu Tower - Agus Komarudin; Kholil Kholil; Toto Hardiyanto (Jurnal Syntax Transformation, 2022)
The purpose of the study is to find out and analyze the influence of personal factors and K3 management variables on work accidents through unsafe actions on indonesia construction project one Tower PT. Bintai Kindenko Engineering Indonesia. The sample in the study was 100 people. Data analysis tools use Smart PLS 3.0 by testing inner models, outer models and hypothesis testing. The results showed that personal factor variables had a significant effect on unsafe actions. K3 management variables have been shown to have a significant effect on unsafe actions. Personal factor variables proved to have a significant effect on work accidents K3 management variables were not shown to have a significant effect on work accidents. Unsafe action variables were shown to significantly affect work accidents. Personal factor variables proved to have a significant effect on work accidents through unsafe actions and K3 management variables proved to have a significant effect on work accidents through unsafe actions on the Indonesia One Tower PT construction project. Bintai Kindenko Engineering Indonesia